2013
DOI: 10.1057/sub.2012.31
|View full text |Cite
|
Sign up to set email alerts
|

Human presence: Towards a posthumanist approach to experience

Abstract: Actor-Network Theory and Latour's principle of symmetry between human and nonhuman creatures was developed as a methodological 'grip' to encourage analysts to investigate sociomaterial configurations rather than defining them before empirical study. In order to adjust the principle of symmetry to the scale of experience, it is argued that what is co-present must be in focus in empirical research as this is what experience relies on. In discussion with Marxist empirical materialism and with studies from the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…It is also consistent with work, within and outside psychology, which explores a web of people and objects together, as already noted (e.g. Sorensen, 2013). However, this notion of a dispersed or distributed person-in-context is again, of course, considerably at odds with common sense notions of the person as contained and agentic.…”
Section: The Discursive Subject: Problems and Resolutionssupporting
confidence: 86%
“…It is also consistent with work, within and outside psychology, which explores a web of people and objects together, as already noted (e.g. Sorensen, 2013). However, this notion of a dispersed or distributed person-in-context is again, of course, considerably at odds with common sense notions of the person as contained and agentic.…”
Section: The Discursive Subject: Problems and Resolutionssupporting
confidence: 86%
“…It's just nice to see them there, but you can still concentrate and be in small groups'. The 'togetherness', connectedness or 'presence' (Sørensen 2013) fosters a sense of belonging and group identity. Bissell (2010, 272) writes of the non-verbal development of affective atmosphere which is perceived and sensed through the body and forms part of 'the ubiquitous backdrop' which is forceful and affects the ways in which spaces are inhabited.…”
Section: Methodsmentioning
confidence: 99%
“…Applying the principle of symmetry 6 in classroom studies, Sørensen (2013) found children to sometimes be configured as a homogeneous group, a team opposite to the teacher, while in some situations teacher and children were configured as one. Reading this diffractively with the drawing above (figure 3) produced different ways of perceiving this picture: the children could be seen as one team, looking at the book, with the teacher and the book as opposite.…”
Section: Focus On Activitiesmentioning
confidence: 99%